Physical Education Training for Disabled Wrestlers (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Wrestling is a sport that requires strength, skill and determination, and it is not limited to any particular group of individuals. Realizing the importance of creating opportunities for people with disabilities, the world of sports has made significant strides towards inclusion. Organizing physical training sessions for wrestlers with disabilities is an important step towards the development of an inclusive sports community. This article explores key considerations and strategies related to creating an environment that welcomes and supports wrestlers with disabilities.